2009
DOI: 10.3171/2009.1.focus0915
|View full text |Cite
|
Sign up to set email alerts
|

Management of anterior inferior cerebellar artery aneurysms: an illustrative case and review of literature

Abstract: Aneurysms of the anterior inferior cerebellar artery (AICA) are relatively rare among intracranial aneurysms. They can occur in 1 of 3 regions of the AICA: 1) craniocaudal (high or low riding), 2) mediolateral-premeatal (proximal), and 3) meatal-postmeatal (distal). The management strategies for treatment differ according to the location and configuration of the aneurysm. The existing body of neurosurgical literature contains articles published on aneurysms arising from the AICA near the basilar artery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 56 publications
3
38
0
Order By: Relevance
“…14,52 In addition, most patients treated with complete petrosectomy suffered long-term facial nerve palsies. 6,18 These results reinforce the intuitive point that labyrinth-sacrificing approaches are less germane in cerebrovascular applications of the petrosal approaches, given the near-ubiquitous presence of serviceable preoperative hearing. Originally conceptualized by Hakuba, 21 a combined posterior petrosal and anterior petrosal approach may be used instead.…”
Section: Posterior Petrosal Approachsupporting
confidence: 74%
See 3 more Smart Citations
“…14,52 In addition, most patients treated with complete petrosectomy suffered long-term facial nerve palsies. 6,18 These results reinforce the intuitive point that labyrinth-sacrificing approaches are less germane in cerebrovascular applications of the petrosal approaches, given the near-ubiquitous presence of serviceable preoperative hearing. Originally conceptualized by Hakuba, 21 a combined posterior petrosal and anterior petrosal approach may be used instead.…”
Section: Posterior Petrosal Approachsupporting
confidence: 74%
“…55 In our review of the literature, we found 34 cases of posterior circulation aneurysms treated via the standard retrolabyrinthine posterior petrosal approach reported in 14 studies over the course of 2 decades (Table 3). 3,6,11,12,14,22,24,32,40,42,43,50,54,56 All aneurysms were completely occluded. In addition, although early morbidity was high (62%; 41% in the form of cranial nerve deficits), it was often transient.…”
Section: Posterior Petrosal Approachmentioning
confidence: 91%
See 2 more Smart Citations
“…[9][10][11][12][13][14][15][16][17][18][19][20][21] Although various surgical approaches have been introduced to access these aneurysms, surgical treatment is often limited due to the complexity of the adjacent neurovascular structure, the presence of brain stem perforators, the narrow and deep surgical field, and the necessity of an experienced surgeon.…”
mentioning
confidence: 99%